Factores determinantes en la prevención y control del vector Aedes aegypti en el cantón Catamayo provincia de Loja. - Cumbicus Rojas, Mauro Geovani (2024)
Aedes aegypti is a stealthy and dangerous vector, so the prevention and control of the vector Aedes aegypti is a high important issue in public health because of this mosquito is the main transmitter of diseases such as dengue, yellow fever, zika and chikungunya. The objective was to analyze the determiners in the prevention and control of the vector Aedes aegypti in the Catamayo canton province of Loja. The methodology used in this research was mixed, quanti- qualitative descriptive and explanatory, with a cross-sectional design, with a sample of 197 inhabitants to whom the surveys were applied, interviews were conducted with the political head of the canton Catamayo, three doctors from the 11D03 health district, a doctor responsible for providing services, a graduate responsible for the health promotion process and an entomologist responsible for the province of Loja. The results suggests help to the reproduction of vectors are: ignorance about the mosquito Aedes aegypti, lack of drinking water supply, inadequate storage, presence of objects capable of storing water inside and outside homes, late disposal of solid waste by the collector trolley in peripheral sectors and lack of implementation of prevention practices by the community: do not have mosquito net, do not use repellent, lack of mesh in doors and windows. In conclusion, the prevention and control of the vector Aedes aegypti in the Catamayo canton requires a comprehensive approach involving community collaboration, the implementation of preventive measures and the improvement of access to information. These findings can be useful for future research and for the implementation of public health policies and programs in the region.